Tinjauan Hukum Terhadap Pembatalan Perjanjian Hibah Karena Pengingkaran - Junaidin; Iksan; Mastorat (Jurnal Hukum Lex Generalis, 2025)
The grant agreement is a unilateral agreement voluntarily made by the donor to the recipient. However, in practice, the grant agreement may be revoked due to a breach or the failure of the recipient to meet specific conditions. This article explores the legal basis for revoking a grant agreement due to breach, from both normative and sociological perspectives. The study finds that under certain conditions, such revocation is legally justified based on principles of justice, good faith, and propriety in civil law.